STATE SOVEREIGNTY IN THE CONTEXT OF THE INFORMATION AGE AND GLOBALIZATION - Brynza, Konstantin (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The features of state sovereignty in the dimension of the information age and globalization are considered. The importance of state sovereignty for ensuring effective development and competitiveness of society is emphasized. The influence of modern conditions on the state of state sovereignty as an important actor of modern global interaction is analyzed. It is determined that in the information age, power largely depends on the ability to produce and control value meanings and cultural codes of society. The importance of identities that characterize modern social interaction at different levels is noted. The contradictions of the universal and the particular are characterized, on the basis of which many conflicts arise. This is confirmed by the multidimensionality of the selection of identities that characterize not only the existence of modern communities, but are also embodied at the personal level. Rapid technological changes, large volumes of information, the need for its adequate interpretation, not only assimilation, but also the production of new knowledge create great demands on a person, on the level of human development. Such challenges to the sovereignty of the state are revealed as instability, uncertainty, polyvariance of social processes both at the global and local, regional levels. The multicentricity of global interaction, the promotion of the influence of non-state actors in the formation of policy at different levels, latency and uncoordination as important characteristics of such interaction also enhance the role of chance and risks for the effective preservation of the sovereignty of modern states. It is noted that «digital divides» based on integration into the latest technologies exacerbate global inequality, consolidate the inheritance of the status of poverty and the displacement of those segments that do not prove their usefulness to global trends and forces of influence to the periphery of development. The activities of modern non-state actors of world politics are most often associated with the interests of economic benefit and originate in the sphere of economics, powerful modern global players represent the sphere of information and communication, communication technologies, artificial intelligence, their influence is based on the possession of media resources, network capabilities and active intervention in the management of cognitive processes at various levels of social life. It is emphasized that the sovereignty of the state requires powerful formation and support of ideological components, protection of unique value meanings and cultural codes of the nation, which determine the modern political space, largely virtualized.